Clinical Characteristics of Hospitalized Individuals Dying With COVID-19 by Age Group in Italy. (7th June 2020) - Palmieri, Luigi; Vanacore, Nicola; Donfrancesco, Chiara; Lo Noce, Cinzia; Canevelli, Marco; Punzo, Ornella; Raparelli, Valeria; Pezzotti, Patrizio; Riccardo, Flavia; Bella, Antonio; Fabiani, Massimo; D'Ancona, Fortunato Paolo; et al.
Abstract: Background: Aim of the present study is to describe characteristics of COVID-19-related deaths and to compare the clinical phenotype and course of COVID-19-related deaths occurring in adults (<65 years) and older adults (≥65 years). Method: Medical charts of 3, 032 patients dying with COVID-19 in Italy (368 aged < 65 years and 2, 664 aged ≥65 years) were revised to extract information on demographics, preexisting comorbidities, and in-hospital complications leading to death. Results: Older adults (≥65 years) presented with a higher number of comorbidities compared to those aged <65 years (3.3 ± 1.9 vs 2.5 ± 1.8, p < .001). Prevalence of ischemic heart disease, atrial fibrillation, heart failure, stroke, hypertension, dementia, COPD, and chronic renal failure was higher in older patients (≥65 years), while obesity, chronic liver disease, and HIV infection were more common in younger adults (<65 years); 10.9% of younger patients (<65 years) had no comorbidities, compared to 3.2% of older patients (≥65 years). The younger adults had a higher rate of non-respiratory complications than older patients, including acute renal failure (30.0% vs 20.6%), acute cardiac injury (13.5% vs 10.3%), and superinfections (30.9% vs 9.8%). Conclusions: Individuals dying with COVID-19 present with high levels of comorbidities, irrespective of age group, but a small proportion of deaths occur in healthy adults with no preexisting conditions. Non-respiratory complications are common, suggesting that the treatment of respiratory conditions needs to be combined with strategies to prevent and mitigate the effects of non-respiratory complications.